2013
DOI: 10.1128/jvi.00645-13
|View full text |Cite
|
Sign up to set email alerts
|

Prime/Boost Immunization with DNA and Adenoviral Vectors Protects from Hepatitis D Virus (HDV) Infection after Simultaneous Infection with HDV and Woodchuck Hepatitis Virus

Abstract: Hepatitis D virus (HDV) superinfection of hepatitis B virus (HBV) carriers causes severe liver disease and a high rate of chronicity. Therefore, a vaccine protecting HBV carriers from HDV superinfection is needed. To protect from HDV infection an induction of virus-specific T cells is required, as antibodies to the two proteins of HDV, p24 and p27, do not neutralize the HBV-derived envelope of HDV. In mice, HDV-specific CD8 ؉ and CD4 ؉ T cell responses were induced by a DNA vaccine expressing HDV p27. In subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In vitro results were promising as stimulation of CD8 T cells with HDV peptides led to an increase on IFN gamma production and cytotoxic activity (206). However, in woodchucks, vaccination (either by HDV proteins, DNA or recombinant viruses) was only effective in preventing HDV infection of naïve animals but not in WHV chronic carriers and, although the course of infection was modified, its utility is still to be proven (207,208).…”
Section: Preventionmentioning
confidence: 96%
“…In vitro results were promising as stimulation of CD8 T cells with HDV peptides led to an increase on IFN gamma production and cytotoxic activity (206). However, in woodchucks, vaccination (either by HDV proteins, DNA or recombinant viruses) was only effective in preventing HDV infection of naïve animals but not in WHV chronic carriers and, although the course of infection was modified, its utility is still to be proven (207,208).…”
Section: Preventionmentioning
confidence: 96%
“…These T cells prevented the development of L-HDAg-expressing tumors in 80 to 100% of immunized mice (9). Moreover, a DNA prime and adenoviral vector boost vaccination with L-HDAg protected woodchucks from HDV in the setting of simultaneous infection with woodchuck hepatitis virus (WHV) and HDV (10). Nisini et al demonstrated a polyspecific but weak CD4 T cell response to HDAg in patients that was related to the resolution of HDV-induced disease activity (11).…”
mentioning
confidence: 99%
“…When co-infected with the Woodchuck Hepatitis Virus (WHV), a relative of HBV within the genus orthohepadnaviruses , the replicating HDV RNP can be packaged into the WHV envelope and secreted into the serum, where it infects neighboring hepatocytes with much higher efficiency than the initial HDV. Although this model is suitable to address some specific questions, e.g., related to the development of HDAg-specific therapeutic vaccines [ 59 ], it relies on WHV and not HBV. One major difference between both viruses is that the WHV envelope proteins probably recognize a receptor different from hNTCP and therefore the model cannot be applied to study the natural infection/co-infection of HBV and HDV.…”
Section: Hdv Infection Modelsmentioning
confidence: 99%